The Effects of Crude Oil and Chemical Dispersant Exposure on Danio rerio (zebrafish) Embryonic Development - Ghiassi, Erfaan (East Carolina University, 2014)
Crude oil has been shown to cause defects in cardiovascular development in a variety of teleost species. We used the zebrafish, Danio rerio as a model to test the effects of oil and dispersant on cardiac development and function during early embryogenesis. The aim of this study is to understand the effects of crude oil and chemical dispersant exposure on the gross anatomy and cellular morphology of cardiac development using the zebrafish (Danio rerio) model. This work was carried out through a histological examination of the phenotypic defects in cardiac development induced by exposure of embryonic zebrafish to crude oil and chemical dispersant. Embryonic exposure to Macondo crude oil and chemical dispersant at 150-250 ppm causes teratogenic effects in cardiac development of zebrafish embryos with phenotypic abberations in form and function evident as early as 48 hpf. Developmental effects on cardiac development include a change in chamber morphology and positioning, coupled with a reduction of cardiac function; leading to cardiac stasis and embryonic death. Specifically, there is progressive yolk sac and cardiac edema, defective and reduced looping of the cardiac chambers, alteration in chamber morphology and positioning, reduction of cardiac function and circulation, and even a reduction in size of the eye and otic vesicle. These results provide a basis for further investigation of the toxicokinetic and toxicodynamic mechanisms through which exposure to crude oil and dispersant cause developmental toxicity. In addition, integrating the results of this study with gene expression profiles obtained from genome-wide transcriptomics at comparable time points promotes the formulation of future hypotheses aiming to more thoroughly understanding the pathways and genetic mechanisms though which PAH toxicity affects the zebrafish heart. Understanding the nature and mechanisms of oil exposure is especially critical for assessing toxicity of PAH contaminated environment.
Keywords: Biology; Histology; Cellular biology; Crude oil; Development; Embryos; Histology; Oil spills; Zebrafish; Zebra danio--Development; Petroleum--Physiological effect; Dispersing agents; Teratogenic agents; Animals--Abnormalities